An Overlooked Natural Hydrogen Evolution Pathway: Ni2+ Boosting H2O Reduction by Fe(OH)2 Oxidation during Low‐Temperature Serpentinization. Issue 45 (7th October 2021) - Song, Han; Ou, Xinwen; Han, Bin; Deng, Haoyu; Zhang, Wenchao; Tian, Chen; Cai, Chunfang; Lu, Anhuai; Lin, Zhang; Chai, Liyuan
Abstract: Natural hydrogen (H2 ) has gained considerable attentions as a renewable energy resource to mitigate the globally increasing environmental concerns. Low‐temperature serpentinization (<200 °C) as a typical water–rock reaction is a major source of the natural H2 . However, the reaction mechanism and the controlling step to product H2 remained unclear, which hinders the further utilization of natural H2 . Herein, we demonstrated that the H2 production rate could be determined by the Fe(OH)2 oxidation during low‐temperature serpentinization. Moreover, the co‐existence of Ni 2+ could largely enhance the H2 production kinetics. With the addition of only 1 % Ni 2+, the H2 production rate was remarkably enhanced by about two orders of magnitude at 90 °C. D2 O isotopic experiment and theoretical calculations revealed that the enhanced H2 production kinetics could be attributed to the catalytic role of Ni 2+ to promote the reduction of H2 O. Abstract : The efficient natural H2 production during Lt‐serpentinization through water reduction by Fe(OH)2 oxidation has been experimentally identified for the first time. This finding provides a new insight to explore the natural H2, which originated from the Ni 2+ rich ultramafic rocks.